2019
DOI: 10.1089/ham.2018.0147
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal Muscle mRNA Response to Hypobaric and Normobaric Hypoxia After Normoxic Endurance Exercise

Abstract: Background: The physiological effects of hypoxia may be influenced by how hypoxia is achieved. The purpose of this study was to determine the effects of recovery in hypobaric hypoxia (HH), normobaric hypoxia (NH), and normobaric normoxia (NN) after endurance exercise on gene expression related to mitochondrial biogenesis, myogenesis, and proteolysis. Methods: Fifteen recreationally trained subjects each cycled for 1 hour before recovering for 4 hours in NN (laboratory atmospheric conditions, 975 m), HH (depres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 47 publications
1
9
0
Order By: Relevance
“…As expected, HR was higher in hypoxic conditions compared to normoxia in response to the increased sympathetic activity and vagal withdrawal. Several studies have further found lower HR in NH vs. HH (Savourey et al, 2003;DiPasquale et al, 2015b;Heinzer et al, 2016;Ross et al, 2019;Aebi et al, 2020) but only during short exposures. In addition, studies examining longer exposures (>8 h) found no difference in HR (Faiss et al, 2013;Richard et al, 2014).…”
Section: Discussionmentioning
confidence: 98%
“…As expected, HR was higher in hypoxic conditions compared to normoxia in response to the increased sympathetic activity and vagal withdrawal. Several studies have further found lower HR in NH vs. HH (Savourey et al, 2003;DiPasquale et al, 2015b;Heinzer et al, 2016;Ross et al, 2019;Aebi et al, 2020) but only during short exposures. In addition, studies examining longer exposures (>8 h) found no difference in HR (Faiss et al, 2013;Richard et al, 2014).…”
Section: Discussionmentioning
confidence: 98%
“…Another factor that has to be taken under consideration when measuring serum myostatin is physical activity of the patients. Results of most recent studies suggest that physical exercise attenuates myostatin gene and protein expression in skeletal muscles directly after training [ 124 , 125 , 126 , 127 , 128 , 129 , 130 , 131 , 132 , 133 , 134 ], while a decrease of physical activity achieved by daily step reduction increased myostatin mRNA expression [ 135 ]. In most studies, serum myostatin levels were found to increase acutely after various exercise types (ultramarathon, aerobic, resistance and high-intensity training) [ 136 , 137 , 138 , 139 , 140 , 141 ], and decrease in the long term as a result of physical training [ 90 , 142 , 143 , 144 , 145 , 146 ].…”
Section: Factors Affecting Myostatin Concentrationmentioning
confidence: 99%
“…Gene expression is affected by hot and cold climates [ 84 , 85 , 86 ] and conditions of low oxygen availability [ 87 , 88 ], though to our knowledge, the effects of such stimuli on CCSs are unknown. Heat acclimation is partially mediated by altered gene expression as an adaptation to peripheral haemodynamic load [ 89 ], and could be one example of an adaptation potentially associated with the reorganisation of specific CCSs.…”
Section: Potential Use Of Ccss In Sport and Exercise Science And Mmentioning
confidence: 99%